Microwaves Devulcanization of SBR Containing Carbon Black - Hirayama, Denise; Scuracchio, Carlos Henrique; Saron, Clodoaldo (Journal of Research Updates in Polymer Science, 2016)
Polymer recycling has been the most suitable alternative for management of plastics waste that are responsible by serious environmental damages. However, the recycling of some polymer materials, such as vulcanized elastomers, is not a trivial process. The recycling of elastomers is a process more complex than the recycling of thermoplastic polymers because the elastomers cannot be remolded by simple heating after vulcanization. Methods for rubber devulcanization has been developed as an interesting alternative for recover flow properties of elastomers, allowing other molding cycle. The aim of this work was to evaluate the effect of the presence of carbon black on devulcanization of styrene-butadiene rubber (SBR) by microwaves and analyze properties of recycled material. The devulcanization by microwaves showed efficiency for rubber compositions with higher content of carbon black incorporated as well as the properties of recycled material showed satisfactory performance for reuse in other products. Microwaves devulcanization of SBR is an important alternative for reuse of rubber waste and decrease of the environmental problem generated with discard of these materials.